Economics for Dummies - Flynn, Sean (Ascent Audio, 2019)
The economy is always changing, but some things are eternal! Economics for Dummies, Third Edition, gives you everything you need to understand our rapidly evolving economy as well as the basics that never change. What's the best way to fight poverty? How can governments boost employment and wage growth? What can be done to protect endangered species and the environment? This book answers all of those questions in simple language while tracking with a traditional introductory economics class. Following in the steps of the first and second editions, the thoroughly updated Third Edition is a useful study guide and supplement to any high school or college level economics class. Discover the ins and outs of irrational consumers. Understand and apply the most powerful tool in economics: the model of supply and demand. Understand the origins and aftermath of financial crises, and more. Economics for Dummies has supplied hundreds of thousands of students with an approachable reference book while also providing an informational outlet for anyone curious about how businesses, consumers, and governments interact to produce and distribute all the goods and services that we enjoy today.